Promo Cashback Dan Kemudahan Transaksi terhadap Keputusan Penggunaan QRIS pada UMKM Berbasis Green Islamic Economic - Ratu Revi Mariska; Astri Pramita Putri; Adelia Novianti; Maya Panorama (Jurnal Penelitian Ekonomi Akuntansi, 2026)
This study aims to evaluate the impact of cashback promotions and ease of transactions on the decision to use QRIS in MSMEs based on a green Islamic economy. The research approach used was quantitative with an associative approach. Data collection was conducted through questionnaires distributed to 100 respondents who used QRIS in MSMEs, using a purposive sampling technique. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics software. The results showed that cashback promotions had a positive and significant influence on the decision to use QRIS, with a calculated t-value of 4.144 and a significance level below 0.001. Furthermore, ease of transactions also showed a positive and significant influence, with a calculated t-value of 5.971 and a significance level below 0.001. Simultaneously, both variables had a significant influence on the decision to use QRIS, with a calculated F-value of 50.014 and a significance level below 0.001. Of the two variables, ease of transactions had a more dominant influence than cashback promotions. These findings indicate that ease of use of digital payment systems is a key factor in increasing the decision to use QRIS among MSMEs, and supports the principles of efficiency and sustainability in a green Islamic economy.